2017
DOI: 10.1002/stem.2705
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Zinc Finger 1 and GA Binding Protein Co-Operate with Sox2 in Regulating the Expression of Yes-Associated Protein 1 in Cancer Cells

Abstract: The transcription factor (TF) yes-associated protein 1 (YAP1) is a major effector of the tumor suppressive Hippo signaling pathway and is also necessary to maintain pluripotency in embryonic stem cells. Elevated levels of YAP1 expression antagonize the tumor suppressive effects of the Hippo pathway that normally represses YAP1 function. High YAP1 expression is observed in several types of human cancers and is particularly prominent in cancer stem cells (CSCs). The stem cell TF Sox2, which marks and maintains C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…Subsequently, our results from luciferase reporter assays involving SOX2 promoter and its mutant as well as ChIP assays further confirmed the direct binding between TAZ/TEAD4 and SOX2 promoter in HNSCC. Noticeably, TAED binding sites in SOX2 promoter identified here were different from those found in other reports whereby two putative YAP/TEAD binding sites were found at upstream (−3759) and downstream ( + 5313) of SOX2 transcription start site (TSS) in murine osteosarcoma cells 35 . We reasoned that it’s conceivable that binding sites for transcriptional factors vary in diverse cell types and biological settings.…”
Section: Discussioncontrasting
confidence: 99%
“…Subsequently, our results from luciferase reporter assays involving SOX2 promoter and its mutant as well as ChIP assays further confirmed the direct binding between TAZ/TEAD4 and SOX2 promoter in HNSCC. Noticeably, TAED binding sites in SOX2 promoter identified here were different from those found in other reports whereby two putative YAP/TEAD binding sites were found at upstream (−3759) and downstream ( + 5313) of SOX2 transcription start site (TSS) in murine osteosarcoma cells 35 . We reasoned that it’s conceivable that binding sites for transcriptional factors vary in diverse cell types and biological settings.…”
Section: Discussioncontrasting
confidence: 99%
“…These data suggest mechanisms whereby members of the SCAN transcription factor family can fine-tune prostate cancer growth by up or downregulating CDC37 transcription and thus decide the outcome of prostate tumorigenesis. It is likely that other MZF1 targets important in tumorigenesis may be regulated in a similar way [17], including oncogenes and pro-tumorigenic genes such as MYC [21], NCAD [31], YAP1 [32], TGF-beta [20], CTSB/L [33], MMP-14 [34], FOXM1 [35], CK17 [36], PAX2 [25], PRAME [24], DR5 [37], AXL [26,38], PKC-alpha [39,40], CD34 , and c-Myb [18]. Besides, MZF1 might play key roles also in tumor microenvironment such as mesenchymal stem cell differentiation into cancer-associated fibroblasts [20].…”
Section: Discussionmentioning
confidence: 99%
“…embryogenesis (21,22,26). Because initial studies of the role of MZF1 in myeloid differentiation and leukemia (18,23), it has been demonstrated that the MZF1-dependent transcriptional changes occur in malignant cellular processes (24,27,28,30,(36)(37)(38)(39)(40)(41)(42)(43), and aberrant expression of MZF1 correlates with poor prognosis of several types of cancers (29,32,34,44,45). However, the contribution of MZF1 to tumorigenesis has not been fully elucidated (20).…”
Section: Discussionmentioning
confidence: 99%